2021
DOI: 10.1007/s00402-021-03943-8
|View full text |Cite
|
Sign up to set email alerts
|

STRYDE versus PRECICE magnetic internal lengthening nail for femur lengthening

Abstract: Introduction Magnetic internal lengthening nails (MILNs) have been used for femoral lengthening to avoid complications associated with external fixation. The titanium version of the MILN (PRECICE®) has been in use since 2011 but had limitations (50–75 lb) in post-operative weight bearing. A new stainless-steel version of the MILN (STRYDE®) allows 150–250 lb of post-operative weight bearing. The aim is to compare the outcomes of using these two different MILNs for both unilateral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(36 reference statements)
2
8
1
Order By: Relevance
“…26 Based on the calculated odds in this study, implant failure was more likely in the STRYDE cohort. While Galal et al 14 and Robbins and Paley 7 did not mention implant failure, most studies concerning the STRYDE nail have reported on implant failures comparable to our results. 8,10,21,23,24 This finding appears to be specific to the STRYDE nail since neither we nor previous studies observed nail or locking bolt breakage as a common complication in patients treated with the conventional PRECICE nail.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…26 Based on the calculated odds in this study, implant failure was more likely in the STRYDE cohort. While Galal et al 14 and Robbins and Paley 7 did not mention implant failure, most studies concerning the STRYDE nail have reported on implant failures comparable to our results. 8,10,21,23,24 This finding appears to be specific to the STRYDE nail since neither we nor previous studies observed nail or locking bolt breakage as a common complication in patients treated with the conventional PRECICE nail.…”
Section: Discussionsupporting
confidence: 86%
“…There was no relevant difference in terms of distraction and consolidation indices between the STRYDE and PRECICE cohort, in contrast to the results of Galal et al, 14 who reported a statistically significant lower distraction rate and a statistically significant higher bone healing index for their STRYDE compared to their PRECICE cohort. However, bone healing seemed to be affected in patients treated with the STRYDE nail in our cohort, since these patients were more likely to undergo revision surgery due to delayed consolidation in comparison to the PRECICE cohort.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations